A fast ion conductor surface modified graphite negative electrode material and preparation method and application thereof

The lithium chloride precursor is uniformly coated on the graphite surface by low-temperature melting method, and a graphite negative electrode material modified with the fast ion conductor surface was prepared through hydrolysis and heat treatment, which solved the problem of poor electrochemical performance of graphite negative electrode materials at low temperatures and high currents, and achieved higher ionic conductivity and better rate performance.

CN118198242BActive Publication Date: 2025-03-18ANHUI CHAOYUE ENVIRONMENTAL TECH CO LTD +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410051325.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-12
Publication Date
2025-03-18
Estimated Expiration
2044-01-12

AI Technical Summary

Technical Problem

Existing graphite anode materials exhibit poor electrochemical performance at low temperatures and high currents, and are prone to formation of dendrite lithium, resulting in battery attenuation and safety problems.

Method used

The lithium-containing chloride precursor is mixed with graphite by low-temperature melting to achieve uniform coating, and then a graphite negative electrode material modified with the surface of the fast ion conductor is prepared by hydrolysis and heat treatment.

Benefits of technology

It improves the ionic conductivity of graphite negative electrode materials, promotes the migration of lithium ions, significantly improves the rate performance and cycle stability, and is suitable for large-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118198242B_ABST
    Figure CN118198242B_ABST
Patent Text Reader

Abstract

The present invention relates to a graphite negative electrode material with fast ion conductor surface modification, a preparation method and an application. The preparation method comprises the following steps: S1. melting a lithium chloride at low temperature and crushing it to obtain a low melting point lithium chloride precursor; S2. mixing the heat-treated graphite with the low melting point lithium chloride precursor evenly and performing a secondary heat treatment to obtain graphite coated with the low melting point lithium chloride precursor; S3. dissolving the graphite coated with the low melting point lithium chloride precursor and performing a heat treatment to obtain a graphite negative electrode material with fast ion conductor surface modification. The present invention performs surface modification of graphite based on a low temperature melting method, has a simple coating method, has low energy consumption, and is suitable for large-scale application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a graphite negative electrode material with a fast ion conductor surface modified, a preparation method and an application thereof. Background Art

[0002] Graphite anode is the most widely used anode material in lithium-ion batteries, and is widely used in 3C products, power batteries, and energy storage batteries. However, the low potential of the graphite anode causes it to react with the electrolyte during discharge, forming a solid electrolyte film on the surface. The ionic conductivity of this film is low, resulting in slow diffusion kinetics of lithium ions and greater polarization. When cycling at low temperature or high current, on the one hand, lithium ions are difficult to embed into the graphite anode, resulting in low graphite utilization and a significant decrease in specific capacity; on the other hand, a large overpotential will cause the deposition of dendrite lithium on the surface of the graphite anode, which will not only cause side reactions and battery attenuation, but may also cause the battery to short-circuit and lead to safety problems.

[0003] At present, there are two main ways to solve the above problems. One is to reduce the thickness of the electrolyte film on the graphite surface, and the other is to improve the lithium ion conductivity of the electrolyte film. Both methods help to reduce the migration time of lithium ions on the graphite surface, thereby improving the electrochemical performance of the graphite negative electrode at low temperature and high current. The formation of the electrolyte interface film can be achieved by the reduction of the electrolyte on the graphite surface. Therefore, by regulating the composition of the electrolyte, the composition, morphology, thickness, etc. of the electrolyte interface film can be changed, thereby changing its ionic conductivity. In addition, an interface film can also be formed on the surface by artificially coating the surface of graphite, and the rapid migration of lithium ions can be achieved by selective interface modification. For example, the patent with publication number CN115836414A discloses an atomic layer deposition method for an ion conductive coating for fast charging of lithium batteries. A layer of Li3BO3-Li2CO3 solid electrolyte film is deposited on the graphite surface by atomic layer deposition (ALD), which has a higher ionic conductivity (>2×10 - 6 S / cm), effectively improving the rate performance of graphite anode and the cycle stability under high current.

[0004] However, the main difficulty in coating the graphite negative electrode to achieve high ionic conductivity of the interface film is how to evenly coat the solid electrolyte with high ionic conductivity on the graphite surface. The Li3BO3-Li2CO3 solid electrolyte coated by the ALD method of the above patent not only has a complex coating method and is not suitable for mass production, but also the conductivity of the coated solid electrolyte material is still low. Summary of the invention

[0005] Based on this, in order to solve the technical problems existing in the current prior art, the purpose of the present invention is to provide a graphite negative electrode material with surface modification of a fast ion conductor, a preparation method and an application thereof. The coating method is simple, the energy consumption is low, and it is suitable for large-scale application.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] The present invention provides a method for preparing a fast ion conductor surface-modified graphite negative electrode material, comprising the following steps:

[0008] S1. After melting the lithium chloride at low temperature, crushing it to obtain a low melting point lithium chloride precursor;

[0009] S2. After the heat-treated graphite is uniformly mixed with the low-melting-point lithium-chloride precursor, a secondary heat treatment is performed to obtain a low-melting-point lithium-chloride precursor-coated graphite;

[0010] S3. The graphite coated with the low melting point lithium chloride precursor is dissolved and heat treated to obtain a graphite negative electrode material with a surface modified with a fast ion conductor.

[0011] The invention mixes and melts lithium-containing chlorides to prepare a low-melting-point lithium-containing chloride precursor, mixes the low-melting-point lithium-containing chloride with a graphite negative electrode in a certain ratio, and realizes uniform coating by infiltration of the molten chloride on the graphite surface; the coated graphite is further washed with water to remove Cl ions therein, and a graphite negative electrode material with a fast ion conductor surface modified is prepared in combination with further heat treatment; the invention performs surface modification of graphite based on a low-temperature melting method, has a simple coating method, has low energy consumption, and is suitable for large-scale application.

[0012] As a further improvement of the above scheme of the present invention, in step S1, the lithium-containing chloride is obtained by mixing LiCl and AlCl3.

[0013] As a further improvement of the above scheme of the present invention, in step S1, the lithium-containing chloride is composed of LiCl, AlCl3, MCl n The mixture is obtained, wherein M is at least one of Nb, Ta, Si, Ge, Ti, Sn, Mo, Zr, and Ga, and n is a positive integer and 3≤n≤6.

[0014] As a further improvement of the above scheme of the present invention, in terms of molar ratio, LiCl, AlCl3, MCl n The mixing ratio is 1:1-x:x, and the expression of the lithium chloride precursor is LiAl 1-x M x Cl 4+y , where 0≤x≤1, 0≤y≤1.

[0015] As a further improvement of the above solution of the present invention, in the step S1, the low temperature melting is carried out by keeping the temperature at 200°C-400°C for 1-5h;

[0016] And / or, in the step S1, the particle size of the lithium-containing chloride precursor obtained by crushing is less than 1 micron.

[0017] As a further improvement of the above solution of the present invention, in step S2, the heat treatment method of the graphite is: heat treating the graphite in an air atmosphere at 400°C-500°C for 0.5-3h, so that C on the graphite surface is oxidized to form C=O bonds, thereby increasing the polarity of the surface.

[0018] As a further improvement of the above scheme of the present invention, in step S2, the mixing ratio of the heat-treated graphite and the lithium-containing chloride precursor is 100-a:a by mass ratio, where a is a positive number less than 5.

[0019] As a further improvement of the above solution of the present invention, in step S2, the secondary heat treatment is carried out at 150°C-400°C for 1-5 hours.

[0020] As a further improvement of the above scheme of the present invention, in step S3, the hydrolysis method is: mixing and stirring the graphite coated with the low melting point lithium chloride precursor with deionized water, an acidic solution or an alkaline solution, and drying at 80-150° C.;

[0021] And / or, in step S3, the heat treatment is carried out under an inert atmosphere at 500° C.-1000° C. for 10-60 min.

[0022] The invention provides a fast ion conductor surface-modified graphite negative electrode material, which is prepared by the method for preparing the fast ion conductor surface-modified graphite negative electrode material as described above.

[0023] The present invention proposes the use of the above-mentioned graphite negative electrode material with a surface modified with a fast ion conductor in a lithium battery.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. The present invention mixes lithium-containing polychlorides and melts them to prepare a low-melting-point lithium-containing chloride precursor, mixes the low-melting-point lithium-containing chloride with a graphite negative electrode in a certain ratio, and utilizes the molten chloride to infiltrate the graphite surface to achieve uniform coating; the coated graphite is further washed with water to remove Cl ions therein, and a graphite negative electrode material with a fast ion conductor surface modified is prepared in combination with further heat treatment; the present invention performs surface modification of graphite based on a low-temperature melting method, has a simple coating method, has low energy consumption, and is suitable for large-scale application.

[0026] 2. The low-temperature melting method of the present invention can achieve the adjustability of the coating layer. In addition to Al chloride, various ions such as Si, Ge, and Nb can also be added. At the same time, the content of Li ions can also be adjusted within a certain range.

[0027] 3. The surface modification layer prepared by hydrolysis and heat treatment in the present invention has higher ionic conductivity, and the ionic conductivity is as high as 10 -5 S / cm, which can effectively promote the migration of lithium ions in the coating layer and achieve better rate performance of the graphite negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a schematic diagram of LiAlCl4 coated graphite by low temperature melting method in Example 1 of the present invention;

[0029] Figure 2 This is a comparative SEM image of the graphite material before and after coating in Example 1 of the present invention;

[0030] Figure 3 This is the AC impedance diagram of the LiAlO2 electrolyte prepared in Example 1 of the present invention;

[0031] Figure 4 The first charge and discharge comparison curves of the graphite negative electrode materials prepared in Example 1 and Comparative Examples 1-3 of the present invention are shown;

[0032] Figure 5 This is a comparison chart of the rate performance of graphite negative electrode materials prepared in Example 1 of the present invention and Comparative Examples 1-3;

[0033] Figure 6 This is a comparison chart of the cycle performance of the graphite negative electrode materials prepared in Example 1 of the present invention and Comparative Examples 1-3. DETAILED DESCRIPTION

[0034] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0036] Example 1

[0037] This embodiment provides a graphite negative electrode material with a fast ion conductor surface modified, and the preparation method thereof comprises the following steps:

[0038] S1. After mixing LiCl and AlCl3 in a molar ratio of 1:1, the mixture was heated to 200°C and kept at 200°C for 1h. After cooling, the product was crushed by ball milling to obtain a lithium chloride precursor LiAlCl4 having a particle size of 500nm;

[0039] S2. The graphite was heated to 400 ° C in an air atmosphere and kept at 400 ° C for 1 hour to obtain preheated graphite; the preheated graphite was mixed with a lithium chloride precursor LiAlCl4 in a mass ratio of 99:1, heated to 200 ° C and kept at 200 ° C for 1h to obtain LiAlCl4-coated graphite;

[0040] S3. The obtained LiAlCl4-coated graphite is added to 1M ammonia water and stirred for 5 hours for hydrolysis, and the Cl ions in LiAlCl4 are replaced by OH ions; then, it is heated to 500°C in an inert atmosphere and kept at 500°C for 1 hour to obtain a graphite negative electrode material with a fast ion conductor surface modified: LiAlO2-coated graphite (OC-Gr).

[0041] Please combine Figure 1 , Figure 1 This is a schematic diagram of the preparation of LiAlCl4-coated graphite by the low-temperature melting method of this embodiment. When heated above the melting point, LiAlCl4 melts into a liquid state and is adsorbed on the graphite surface to form a continuous coating layer.

[0042] Please combine Figure 2 , Figure 2 Before coating ( Figure 2 Left), Back( Figure 2 Right) SEM image of graphite negative electrode, from which we can see that before coating ( Figure 2 The graphite surface of the left) is relatively smooth, while after coating ( Figure 2 A coating layer appears on the graphite surface (right), which is mainly in the form of fine particles.

[0043] The lithium chloride precursor LiAlCl4 prepared in this embodiment was placed in 1M ammonia water and stirred for 5 hours for hydrolysis, and then heated to 500°C in an inert atmosphere and kept at 500°C for 1 hour to obtain LiAlO2; the prepared LiAlO2 was pressed into a disc with a diameter of 12 mm and a thickness of about 1 mm by a tablet pressing mold at a pressure of 300 MPa, and the impedance of the disc was tested at a pressure of 50 MPa. The test results are shown in FIG. Figure 3 ,from Figure 3 It can be seen that the ionic conductivity of the prepared LiAlO2 is 2.01×10 -5 S / cm(25℃).

[0044] Comparative Example 1

[0045] This comparative example uses conventional graphite negative electrode material (Gr).

[0046] Comparative Example 2

[0047] This comparative example provides a graphite negative electrode material, and the preparation method thereof comprises the following steps:

[0048] S1. After mixing LiCl and AlCl3 in a molar ratio of 1:1, the mixture was heated to 200°C and kept at 200°C for 1h. After cooling, the product was crushed by ball milling to obtain a lithium chloride precursor LiAlCl4 having a particle size of 500nm;

[0049] S2. The graphite and the lithium chloride precursor LiAlCl4 were mixed in a mass ratio of 99:1, heated to 200 ° C and kept at 200 ° C for 1h to obtain LiAlCl4-coated graphite;

[0050] S3. The LiAlCl4-coated graphite was added to 1M ammonia water and stirred for 5 h for hydrolysis, and the Cl ions in the LiAlCl4 were replaced by OH ions; then, the mixture was heated to 500°C in an inert atmosphere and kept at 500°C for 1 h to obtain a graphite negative electrode material: LiAlO2-coated graphite (C-Gr).

[0051] Comparative Example 3

[0052] This comparative example provides a graphite negative electrode material. The graphite is heated to 400° C. in an air atmosphere and kept at 400° C. for 1 hour to obtain a graphite negative electrode material (O-Gr).

[0053] Test Case

[0054] The graphite negative electrode material with a surface modified with a fast ion conductor prepared in Example 1 and the graphite negative electrode materials prepared in Comparative Examples 1-3 are prepared into button-type lithium-ion batteries, and the preparation method is as follows: the graphite negative electrode material, acetylene black, and PVDF are mixed in a mass ratio of 8:1:1, and NMP is added to form a slurry, wherein the solid content of the slurry is about 40%; the evenly mixed slurry is coated on a copper foil, and then dried in an oven at 80° C. to obtain a graphite electrode sheet; the dried electrode sheet is punched into a disc with a diameter of 12 mm with a punch to obtain a graphite electrode; and the graphite electrode is matched with a lithium metal electrode to assemble into a button-type lithium-ion battery.

[0055] The button-type lithium-ion batteries prepared above were tested for initial charge and discharge, rate performance, and cycle performance between 0V and 3V, and the current ranged from 0.1C to 2C. The test results are shown in Figure 4 , Figure 5 , Figure 6 .from Figure 4 , Figure 5 , Figure 6 It can be seen that:

[0056] from Figure 4 It can be seen that when charging and discharging at 0.1C, the first charging capacity of the untreated graphite negative electrode (Gr) of comparative example 1 is about 375mAh / g, and the coulomb efficiency is about 87.79%; the first charging capacity of the graphite directly coated in comparative example 2 (C-Gr) is about 37mAh / g, and the coulomb efficiency is about 87.91%; Figure 5 From the rate performance point of view, the rate performance of the graphite (C-Gr) directly coated in Comparative Example 2 is not much different from that of the untreated graphite negative electrode (Gr) in Comparative Example 1, indicating that the coating effect of the unoxidized graphite is not good;

[0057] from Figure 4 It can be seen that when charging and discharging at 0.1C, the first charging capacity of the untreated graphite negative electrode (Gr) of comparative example 1 is about 375mAh / g, and the coulombic efficiency is about 87.79%; the first charging capacity of the graphite (O-Gr) after oxidation treatment in comparative example 3 is about 355mAh / g, and the coulombic efficiency is about 86.61%; the first charging capacity of the coated graphite (OC-Gr) after oxidation treatment in Example 1 is about 400mAh / g, and the coulombic efficiency is about 89.12%; it can be seen that the well-coated graphite negative electrode exhibits higher specific capacity and first coulombic efficiency;

[0058] When the current increases, the coated graphite anode exhibits a higher specific capacity. Figure 5 As shown in the figure, when the current increases to 2C, the specific capacity of the untreated graphite in Comparative Example 1 drops to about 50mAh / g, while the graphite after oxidation coating in Example 1 still maintains a specific capacity of 150mAh / g, showing a better rate performance; by comparing the cycle stability of the graphite negative electrode before and after coating, it can be seen that the capacity of the coated graphite after 100 cycles at a current of 0.5C is also higher ( Figure 6 ).

[0059] Example 2

[0060] This embodiment provides a graphite negative electrode material with a fast ion conductor surface modified, and the preparation method thereof comprises the following steps:

[0061] S1. After mixing LiCl and AlCl3 in a molar ratio of 1:1, the mixture was heated to 200°C and kept at 200°C for 1h. After cooling, the product was crushed by ball milling to obtain a lithium chloride precursor LiAlCl4 having a particle size of 500nm;

[0062] S2. The graphite was heated to 400 ° C in an air atmosphere and kept at 400 ° C for 1 hour to obtain preheated graphite; the preheated graphite was mixed with a lithium chloride precursor LiAlCl4 in a mass ratio of 99:1, heated to 200 ° C and kept at 200 ° C for 1h to obtain LiAlCl4-coated graphite;

[0063] S3. The obtained LiAlCl4-coated graphite is added to 1M ammonia water and stirred for 5 hours for hydrolysis, and the Cl ions in LiAlCl4 are replaced by OH ions; then, it is heated to 1000°C in an inert atmosphere and kept at 1000°C for 10 minutes to obtain a graphite negative electrode material with a fast ion conductor surface modified: LiAlO2-coated graphite (OC-Gr).

[0064] The fast ion conductor surface modified graphite negative electrode material prepared in this embodiment is prepared into a button lithium ion battery, and the preparation method is as follows: after the graphite negative electrode material, acetylene black and PVDF are mixed in a mass ratio of 8:1:1, NMP is added to prepare a slurry, and the solid content of the slurry is about 40%; the mixed slurry is coated on a copper foil, and then dried in an oven at 80°C to obtain a graphite electrode sheet; the dried electrode sheet is punched into a 12mm diameter disc to obtain a graphite electrode; the graphite electrode is matched with a lithium metal electrode to assemble a button lithium ion battery. The prepared button lithium ion battery is charged and discharged between 0V and 3V, and the current size is from 0.1C to 2C. When charged and discharged at 0.1C, the first charging capacity is about 395mAh / g, and the coulomb efficiency is about 90.1%. When the current is increased to 2C, the specific capacity of 205mAh / g can still be maintained, showing a better rate performance.

[0065] Example 3

[0066] This embodiment provides a graphite negative electrode material with a fast ion conductor surface modified, and the preparation method thereof comprises the following steps:

[0067] S1. LiCl, AlCl3, and NbCl5 were mixed evenly in a molar ratio of 1:0.5:0.5, heated to 200°C and kept at 200°C for 1 hour, and then the product was crushed by ball milling after cooling to obtain a lithium chloride precursor LiAl with a particle size of 500 nm. 0.5 Nb 0.5 Cl5;

[0068] S2. The graphite is heated to 400°C in an air atmosphere and kept at 400°C for 1 hour to obtain preheated graphite; the preheated graphite is mixed with a lithium chloride precursor LiAl 0.5 Nb 0.5 Cl5 was mixed in a mass ratio of 99:1, heated to 200°C and kept at 200°C for 1h to obtain LiAl 0.5Nb 0.5 Cl5 coated graphite;

[0069] S3. 10g of LiAl 0.5 Nb 0.5 The Cl5-coated graphite was added to 20 ml of distilled water and stirred for 5 h for hydrolysis. 0.5 Nb 0.5 The Cl ions in Cl5 are replaced by OH ions; then, the mixture is heated to 1000°C in an inert atmosphere and kept at 1000°C for 10 minutes to obtain a graphite negative electrode material with a fast ion conductor surface modified: Li2AlNbO5-coated graphite.

[0070] The graphite negative electrode material modified with the surface of the fast ion conductor prepared in this embodiment is prepared into a button-type lithium ion battery, and the preparation method is as follows: after the graphite negative electrode material, acetylene black and PVDF are mixed in a mass ratio of 8:1:1, NMP is added to prepare a slurry, and the solid content of the slurry is about 40%; the mixed slurry is coated on a copper foil, and then dried in an oven at 80°C to obtain a graphite electrode sheet; the dried electrode sheet is punched into a 12mm diameter disc to obtain a graphite electrode; the graphite electrode is matched with a lithium metal electrode to assemble into a button-type lithium ion battery. The prepared button-type lithium ion battery is charged and discharged between 0V and 3V, and the current size is from 0.1C to 2C. When charged and discharged at 0.1C, the first charging capacity is about 390mAh / g, the coulomb efficiency is about 90.1%, and when the current is increased to 2C, the specific capacity of 280mAh / g can still be maintained.

[0071] The LiAl prepared in this example 0.5 Nb 0.5 The Cl5 sample was reacted in distilled water alone and kept at 500°C for 1 hour to obtain Li2AlNbO5 and its ionic conductivity was tested. The Li2AlNbO5 obtained in this embodiment was pressed into a disc with a diameter of 12 mm and a thickness of about 1 mm by a tablet pressing mold at a pressure of 300 MPa. The impedance of the disc was tested at a pressure of 50 MPa, and the ionic conductivity of Li2AlNbO5 was 5.1×10 -5 S / cm(25℃).

[0072] Example 4

[0073] This embodiment provides a graphite negative electrode material with a fast ion conductor surface modified, and the preparation method thereof comprises the following steps:

[0074] S1. LiCl, AlCl3, and TaCl5 were mixed evenly in a molar ratio of 1:0.5:0.5, heated to 200°C and kept at 200°C for 1 hour, and then the product was crushed by ball milling after cooling to obtain a lithium chloride precursor LiAl with a particle size of 450 nm. 0.5 Ta0.5 Cl5;

[0075] S2. The graphite is heated to 400°C in an air atmosphere and kept at 400°C for 30 minutes to obtain preheated graphite; the preheated graphite is mixed with a lithium chloride precursor LiAl 0.5 Ta 0.5 Cl5 was mixed in a mass ratio of 99:1, heated to 350°C and kept at 350°C for 1h to obtain LiAl 0.5 Ta 0.5 Cl5 coated graphite;

[0076] S3. 10g of LiAl 0.5 Ta 0.5 The Cl5-coated graphite was added to 20 ml of distilled water and stirred for 5 h for hydrolysis. 0.5 Ta 0.5 The Cl ions in Cl5 are replaced by OH ions; then, the mixture is heated to 1000°C in an inert atmosphere and kept at 1000°C for 10 minutes to obtain a graphite negative electrode material with a fast ion conductor surface modified: Li2AlTaO5-coated graphite.

[0077] The graphite negative electrode material modified with the surface of the fast ion conductor prepared in this embodiment is prepared into a button-type lithium-ion battery. The preparation method is as follows: after the graphite negative electrode material, acetylene black and PVDF are mixed in a mass ratio of 8:1:1, NMP is added to prepare a slurry, and the solid content of the slurry is about 40%; the mixed slurry is coated on a copper foil, and then dried in an oven at 80°C to obtain a graphite electrode sheet; the dried electrode sheet is punched into a 12mm diameter disc to obtain a graphite electrode; the graphite electrode is matched with a lithium metal electrode to assemble a button-type lithium-ion battery. The prepared button-type lithium-ion battery is charged and discharged between 0V and 3V, and the current size is from 0.1C to 2C. When charged and discharged at 0.1C, the first charging capacity is about 390mAh / g, and the coulomb efficiency is about 90.1%. When the current is increased to 2C, the specific capacity of 274mAh / g can still be maintained.

[0078] The LiAl prepared in this example 0.5 Ta 0.5 The Cl5 sample was reacted in distilled water alone and kept at 500°C for 1 hour to obtain Li2AlTaO5 and its ionic conductivity was tested. The Li2AlTaO5 obtained in this embodiment was pressed into a disc with a diameter of 12 mm and a thickness of about 1 mm by a tablet pressing mold at a pressure of 300 MPa. The impedance of the disc was tested at a pressure of 50 MPa, and the ionic conductivity of Li2AlTaO5 was 4.1×10 -5 S / cm(25℃).

[0079] Example 5

[0080] This embodiment provides a graphite negative electrode material with a fast ion conductor surface modified, and the preparation method thereof comprises the following steps:

[0081] S1. LiCl, AlCl3, NbCl5, and TaCl5 were mixed evenly in a molar ratio of 1:0.5:0.25:0.25, heated to 200°C and kept at 200°C for 1 hour, and then the product was ground by grinding after cooling to obtain a lithium chloride precursor LiAl with a particle size of 450 nm. 0.5 Nb 0.25 Ta 0.25 Cl5;

[0082] S2. The graphite is heated to 400°C in an air atmosphere and kept at 400°C for 30 minutes to obtain preheated graphite; the preheated graphite is mixed with a lithium chloride precursor LiAl 0.5 Nb 0.25 Ta 0.25 Cl5 was mixed in a mass ratio of 99:1, heated to 400°C and kept at 400°C for 1h to obtain LiAl 0.5 Nb 0.25 Ta 0.25 Cl5 coated graphite;

[0083] S3. 10g of LiAl 0.5 Nb 0.25 Ta 0.25 The Cl5-coated graphite was added to 20 ml of distilled water and stirred for 5 h for hydrolysis. 0.5 Nb 0.25 Ta 0.25 The Cl ions in Cl5 were replaced by OH ions; then the mixture was heated to 1000°C in an inert atmosphere and kept at 1000°C for 10 min to obtain a graphite negative electrode material modified with a fast ion conductor surface: Li2AlNb 0.5 Ta 0.5 O5 coated graphite.

[0084] The graphite negative electrode material modified with the surface of the fast ion conductor prepared in this embodiment is prepared into a button-type lithium-ion battery. The preparation method is as follows: after the graphite negative electrode material, acetylene black and PVDF are mixed in a mass ratio of 8:1:1, NMP is added to prepare a slurry, and the solid content of the slurry is about 40%; the mixed slurry is coated on a copper foil, and then dried in an oven at 80°C to obtain a graphite electrode sheet; the dried electrode sheet is punched into a 12mm diameter disc to obtain a graphite electrode; the graphite electrode is matched with a lithium metal electrode to assemble a button-type lithium-ion battery. The prepared button-type lithium-ion battery is charged and discharged between 0V and 3V, and the current size is from 0.1C to 2C. When charged and discharged at 0.1C, the first charging capacity is about 390mAh / g, and the coulomb efficiency is about 90.1%. When the current is increased to 2C, the specific capacity of 300mAh / g can still be maintained.

[0085] The LiAl prepared in this example 0.5 Nb 0.25 Ta 0.25 The Cl5 sample was reacted in distilled water and then kept at 500℃ for 1 hour to obtain Li2AlNb 0.5 Ta 0.5 O5 and tested its ionic conductivity. 0.5 Ta 0.5 O5 was pressed into a disc with a diameter of 12 mm and a thickness of about 1 mm by a tablet pressing mold at a pressure of 300 MPa. The impedance of the disc was tested at a pressure of 50 MPa to obtain Li2AlNb 0.5 Ta 0.5 The ionic conductivity of O5 is 8.1×10 -5 S / cm(25℃).

[0086] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0087] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a fast ion conductor surface-modified graphite negative electrode material, characterized in that: The following steps are involved: S1. After melting the lithium chloride at low temperature, crushing it to obtain a low melting point lithium chloride precursor; S2. After the heat-treated graphite is uniformly mixed with the low-melting-point lithium-chloride precursor, a secondary heat treatment is performed to obtain a low-melting-point lithium-chloride precursor-coated graphite; S3. After the low melting point lithium chloride precursor coated graphite is dissolved, heat treated to obtain a graphite negative electrode material modified with a fast ion conductor surface; In step S1, the lithium chloride precursor is expressed as LiAl 1-x M x Cl 4+y , wherein 0≤x≤1, 0≤y≤1; M is at least one of Nb, Ta, Si, Ge, Ti, Sn, Mo, Zr, and Ga; In step S2, the heat treatment method of the graphite is: heat treating the graphite in an air atmosphere at 400°C-500°C for 0.5-3h; in terms of mass ratio, the mixing ratio of the heat-treated graphite and the lithium chloride precursor is 100-a:a, where a is a positive number less than 5.

2. The method for preparing a fast ion conductor surface-modified graphite negative electrode material according to claim 1, characterized in that: In the step S1, the lithium-containing chloride is obtained by mixing LiCl and AlCl3.

3. The method for preparing a fast ion conductor surface-modified graphite negative electrode material according to claim 1, characterized in that: In step S1, the lithium-containing chloride is composed of LiCl, AlCl3, MCl n The mixture is obtained, where n is a positive integer and 3≤n≤6.

4. The method for preparing a fast ion conductor surface-modified graphite negative electrode material according to claim 3, characterized in that: In terms of molar ratio, LiCl, AlCl3, MCl n The mixing ratio is 1:1-x:x, where x is not equal to 0.

5. The method for preparing a fast ion conductor surface-modified graphite negative electrode material according to claim 1, characterized in that: In the step S1, the low temperature melting is carried out at 200°C-400°C for 1-5 hours; And / or, in the step S1, the particle size of the lithium-containing chloride precursor obtained by crushing is less than 1 micron.

6. The method for preparing a fast ion conductor surface-modified graphite negative electrode material according to claim 1, characterized in that: In step S2, the secondary heat treatment is carried out at 150°C-400°C for 1-5 hours.

7. The method for preparing a fast ion conductor surface-modified graphite negative electrode material according to claim 1, characterized in that: In the step S3, the hydrolysis method is: mixing and stirring the graphite coated with the low melting point lithium chloride precursor with deionized water, an acidic solution or an alkaline solution, and then drying at 80-150° C.; And / or, in step S3, the heat treatment is carried out under an inert atmosphere at 500° C.-1000° C. for 10-60 min.

8. A graphite negative electrode material with a fast ion conductor surface modified, characterized in that: The negative electrode material is prepared by the method for preparing a graphite negative electrode material with a surface modified with a fast ion conductor as described in any one of claims 1 to 7.

9. Use of the graphite negative electrode material with a fast ion conductor surface modified as claimed in claim 8 in a lithium battery.

Citation Information

Patent Citations

  • Atomic layer deposition method of ionic conductive coating for rapid charging of lithium battery

    CN115836414A

  • LiAlO2 coated modified graphite negative electrode material as well as preparation method and application thereof

    CN113363446A

  • Manganese chloride coated graphite high-rate lithium ion battery negative electrode material and preparation method thereof

    CN113725437A

  • Composite graphite modified material as well as preparation method and application thereof

    CN115663148A